User experience evaluation: E-Learning @ UTM mobile application case study [electronic resource] - Allam Hassan Allam, 1984- (2012)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2012